Frequency of Indications and Types of Enteric Stoma in Surgical Ward of Ayub Teaching Hospital Abbottabad - Rehman, Tahir Ur; Rafiq, Muhammad Kashif; Ashraf, Waqas; Khan, Yousuf Aziz; Sultan, Babar (Indus Journal of Bioscience Research, 2025)
Introduction: Strategic stomas are crucial operations in the management of various gastrointestinal disorders such as intestinal obstruction, perforation, and trauma. It is necessary to examine the frequency of this type of stoma, as well as indications for its treatment and outcomes, in order to improve patient management. Objectives: To determine the frequency of indications, and types of enteric stomas formed in the surgical ward of Ayub Teaching Hospital, Abbottabad and analyze associated outcomes. Materials and Methods: This cross-sectional study was performed in 2024 for six months with 121 patients with stoma formation. The research employed a nonprobability consecutive sampling technique. The demographic information, indications for the creation of a stoma, type of stoma and postoperative complications were recorded. Descriptive statistics in the current study were done using Statistical Package for Social Sciences (SPSS) software version 23. Results: The most common indications for operation were intestinal obstruction, which was seen in 36.4%, and perforation in 28.1%. Loop stomas (58.7%) were the most common, while end stomas (11.6%). Wound infection, which was noted in 15.7% of patients, and stoma retraction in 10.7% of patients were more common in emergency surgeries, which formed 42.3%. Conclusion: The aspects of early diagnosis, optimum preoperative preparation and psychological intervention need to be specifically personalised for the benefit of stoma patients.